Sentiment Analysis Utilizing Modal Expressions - Jang, Ji-won; Kim, Jee-Eun (Institute of British and American Studies, 2017)
This research presents a classification of English modal expressions which affect polarity values in sentiment analysis. Modality, commonly encountered in sentences, conveys various semantic attitudes of a speaker. Because of its special characteristics, the meaning of a modalized sentence is challenging to be correctly interpreted. The sentiment expressed with modal expressions is also difficult to evaluate. In order to increase the accuracy in evaluating sentiment values, modal expressions are collected from movie reviews and analyzed with selected linguistic cues to classify. The classification includes the expressions, its contextual components to co-occur, and the resulting sentiment value. Since it also lists up the classes which have not been dealt with in previous studies, it is expected to contribute performance improvement of a sentiment analysis system. KCI Citation Count: 0